THE IMPORTANCE OF CRITICAL THINKING IN EDUCATION - G`afurova, G`afurova (Журнал иностранных языков и лингвистики, 2023)
This paper describes several notions of critical thinking and emphasizes the value of this skill in education. To encourage active citizenship, which in turn promotes sustainable development, it first discusses certain philosophical and psychological approaches to critical thinking and their influence in national and international educational systems. Second, it emphasizes how critical thinking and content- and language-integrated learning are related (CLIL). Third, it is essential to foster critical thinking for instructors during the teaching process.